PROMOTING LOCAL MANAGEMENT IN GROUNDWATER - Van Steenbergen F. (My University, 2006)
There is a strong case for making greater effort to promote local groundwater management—in addition to other measures that regulate groundwater use. Though scattered, there are several examples—from India, Pakistan, Yemen and Egypt—where groundwater users effectively self-imposed restrictions on the use of groundwater. There are a number of recurrent themes in such spontaneously-developed examples of local regulation: the importance of not excluding potential users; the importance of simple, low transaction cost rules; the power of correct and accessible hydrogeological information; the possibility of making more use of demand and supply management strategies; and the important supportive role of local governments. The case is made, using examples, for actively promoting local groundwater management as an important element in balancing groundwater uses. Two programmes for promoting local groundwater management in South India are described—one focussing on participatory hydrological monitoring, and one focussing on micro-resource planning and training. In both cases the response was very positive and the conclusion is that promoting local groundwater regulation is not difficult, costly or sensitive and can reach the necessary scale quickly.
Keywords: GROUNDWATER MANAGEMENT; SOUTH ASIA; YEMEN; EGYPT; WATER BUDGET; COMMUNITY MANAGEMENT; PARTICIPATORY MONITORING; MICRO-PLANNING